Rendimiento de cerdos en la etapa crecimiento engorde con la adicion de tres programas de alimentacion en la granja “Los Guerreros” - Guerrero Aviles, Irvin Gabriel (2022)
The subject of this research is the performance of pigs in the fattening growth stage with the addition of three feeding programs in the farm "Los Guerreros", carried out in the farm "Los Guerreros", Chillanes, belonging to the province of Bolivar. The objectives of this research were: i) To establish the best feeding program (molasses, sugar cane juice, green guineo plus balanced feed), compared to the control. ii) To determine the weight gain, feed conversions, of the proposed feeding programs. iii) To perform the economic analysis in the cost/benefit ratio. The methodology applied was a randomized complete block experimental design with three replications. Four treatments were obtained T1: Control; T2: Sugar cane juice + 1 kg/day of balanced diet + water. T3: Green banana + 1 kg/day of balanced diet + water. T4: Molasses + 1 Kg/day of balanced diet + Water. An analysis of variance, Tukey's test at 5%, was performed to compare the averages between the treatments to be evaluated. As well as a simple and multiple correlation and regression analysis at 5%. It was determined that cane molasses 1 kg/day of balanced diet + water was the best raw material for feeding pigs in the fattening growth stage during the best reaction evaluated. The best weight gain and feed conversion corresponds to the pigs that received molasses in their feed (T4: Molasses + 1 kg/day of balanced diet + water).